Pick and roll - Blair, Kelsey (2014)
Jazz Smith-Mohapatra is the toughest and best player on her basketball team--and this year she's determined to lead the team to a championship win. But in the last game of the regular season, Jazz sets an offensive move called a pick and roll, sending her opponent onto the floor. Now Jazz's position on the team is in question: there's a Fair Play Commission, and her teammates are suddenly questioning her physical style of play. Will the team have to make it all the way to the pennant without her?
Issued also in electronic format.
Keywords: Basketball stories; Women basketball players -- Juvenile fiction; Basketball -- Fiction; Women basketball players -- Fiction